On the road to a global wireless sensor network - Sosa, Eduardo Omar (2011)
This work has considered the development, testing, configuration and implementation of a wireless sensor network infrastructure. This infrastructure on a testbed scale has been used primarily for research, oriented to an interdisciplinary approach that encompasses the hardware, software, algorithms and data. It sought to demonstrate that the heterogeneity of devices and small existing structures may coalesce into well-organized, large-scale, different existing grids that will enable a quantitative and qualitative research to a much larger scale by addressing the dynamic changes of venues, infrastructure and composition of nodes. Considering that a real implementation is usually a complicated task, we have performed a network simulation and a real testbed. Also a contribution to the establishment of a global network of wireless sensors has been highlighted, distinguishing three sub domains in the global network considered: the existing top network, the sensing devices and the servers.